Correction: Why Do You Believe in God? Relationships between Religious Belief, Analytic Thinking, Mentalizing and Moral Concern. - Anthony Ian Jack; Jared Parker Friedman; Richard Eleftherios Boyatzis; Scott Nolan Taylor (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0149989.].